JURNAL KESEHATAN JURNAL ILMU KESEHATAN STIKES DUTA GAMA KLATEN - Rr. Erni Kusuma Putri (STIKES DUTAGAMA KLATEN, 2022)
Hypertension is often referred to as the silent killer because this disease has no specific symptoms, can attack anyone and at any time, and can cause degenerative diseases, up to death. Based on the background of the problem above, it can be formulated how the pattern of prescribing the use of antihypertensive drugs to outpatients at the Kusuma Main Clinic, Wonosobo City. To determine the pattern of prescribing the use of antihypertensive drugs in outpatients for the January - March 2019 period at the Kusuma Main Clinic, Wonosobo City. This study is a descriptive survey research with quantitative research procedures, data obtained from secondary data taken directly from prescriptions for outpatient hypertension patients for the period January - March 2019 at the Kusuma Main Clinic, Wonosobo City. The highest number and percentage of drug use in patients with hypertension by gender were women, namely 57.69, based on age group > 50 years, namely 76.92%. The active substance that was more widely prescribed was amlodipine, which was 39.22%. The most antihypertensive group was the calcium antagonist group, namely 41.18%. More women suffer from hypertension when they enter menopause, this is due to a decrease in the hormone estrogen. In this case, the related agencies of the Health Department should provide counseling to the public about hypertension management and a healthy lifestyle, especially for those over 50 years old.